Beyond AREDS Formulations, What Is Next for Intermediate Age-Related Macular Degeneration (iAMD) Treatment? Potential Benefits of Antioxidant and Anti-inflammatory Apocarotenoids as Neuroprotectors - Camelo, Serge (Oxid Med Cell Longev, 2020)
Age-related macular degeneration (AMD) is the commonest cause of severe visual loss and blindness in developed countries among individuals aged 60 and older. AMD slowly progresses from early AMD to intermediate AMD (iAMD) and ultimately late-stage AMD. Late AMD encompasses either neovascular AMD (nAMD) or geographic atrophy (GA). nAMD is defined by choroidal neovascularization (CNV) and hemorrhage in the subretinal space at the level of the macula. This induces a rapid visual impairment caused by the death of photoreceptor cells. Intravitreal injection of anti-vascular endothelial growth factor (VEGF) antibodies is the standard treatment of nAMD but adds to the burden of patient care. GA is characterized by slowly expanding photoreceptor, and retinal pigment epithelium (RPE) degeneration patches progressively leading to blindness. There is currently no therapy to cure GA. Late AMD continues to be an unmet medical need representing a major health problem with millions of patients worldwide. Oxidative stress and inflammation are recognized as some of the main risk factors to developing late AMD. The antioxidant formulation AREDS (Age-Related Eye Disease Studies), contains β-carotene, which has been replaced by lutein and zeaxanthin in AREDS2, are given to patients with iAMD but have a limited effect on the incidence of nAMD and GA. Thus, to avoid or slowdown the development of late stages of AMD (nAMD or GA), new therapies targeting iAMD are needed such as crocetin obtained through hydrolysis of crocin, an important component of saffron (Crocus sativus L.), and norbixin derived from bixin extracted from Bixa orellana seeds. We have shown that these apocarotenoids preserved more effectively RPE cells against apoptosis following blue light exposure in the presence of A2E than lutein and zeaxanthin. In this review, we will discuss the potential use of apocarotenoids to slowdown the progression of iAMD, to reduce the incidence of both forms of late AMD.